REVIEW OF COMPARATIVE PEDAGOGICAL RESEARCHES IN THE FIELD OF INFORMATION AND COMMUNICATION COMPETENCE IN EDUCATION SYSTEM - Oksana V. Ovcharuk; Nataliia V. Soroko (Information technologies and learning tools, 2015)
The article deals with the scientific international and Ukrainian experience on the comparative education studies on information and communication competence development by educational process participants, which became the major scientific achievement of staff of Comparative Studies Department for Information and Education Innovations of the Institute of Information Technologies and Learning Tools of NAES of Ukraine. The main obstacles for school teachers to the creation of computer-based learning environment are determined. The development and evaluation of educational process participants’ IT-competence are in the focus of investigation, which need studies to give recommendations to education sphere.